PENGARUH LATIHAN CIRCUIT TRAINING TERHADAP DAYA TAHAN ATLET SEPAKBOLA SSB RUMBAI JUNIOR - Deoledi Deoledi '; Ramadi Ramadi '; Ardiah Juita Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The research was conduted determine effect of exercise Circuit Training againts endurance football athletes SSB Rumbai Junior, The method is experimental research, population is SSB Rumbai Junior 39 people, with a sample 16 people. Sampling technique that puporsive sampling. Instruments used in a research is running with distance 2,4 km, Afterwards, the data proccesed by statistics to examine the normality by using lilifors test at significance level 0,05α. Hypothesis there is a effect of exercise circuit training againts endurance football athletes SSB Rumbai Junior, Data from pretest Circuit Training test as colculated produce Lcount 0,137, Ltable 0,213. IT means Lcount< Ltable. Concluded the data pretest Endurance test were normally distributed. Post test data test produce Lcount 0,137, Ltable 0,213. IT means Lcount< Ltable. Concluded the data post Endurance test were normally distributed. By test analysis produce Tcount 2,595 and Ttable1,753 that Tcount > Ttable it can be concluded Ha accepted. Therefore, there is influence effect of exercise Circuit Training againts endurance football athletes SSB Rumbai JuniorKeyword: Effect of exercise Circuit Training againts Endurance